2017
DOI: 10.17223/18572685/47/15
|View full text |Cite
|
Sign up to set email alerts
|

The Death of V.M. Purishkevich: New Data About the Biography of the Politician-Monarchist

Abstract: Авторское резюме Впервые реконструируются обстоятельства последних дней жизни и смерти известного российского правого политика В.М. Пуришкевича (1870-1920). Опираясь на новые источники, включая неизвестные ранее документы из личного архива Пуришкевича, сохранившегося в фондах библиотеки Свободного университета Брюсселя (Université Libre de Bruxelles), и публикации белогвардейской прессы, авторы опровергают бытующие в литературе мифы и вводят в научный оборот новые факты, позволяющие внести определенные коррект… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The addition of water was shown to act as an extra source for heat loss thereby lowering the temperature within the droplet so that the extent of cracking reactions (and, therefore, subsequent formation of particulates) was reduced. Micro-explosions seem to have been first reported in 1965 [7]. Experimental studies showed that combustion of compound droplets with different volatile fluids may be accompanied by violent explosion of the droplets.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of water was shown to act as an extra source for heat loss thereby lowering the temperature within the droplet so that the extent of cracking reactions (and, therefore, subsequent formation of particulates) was reduced. Micro-explosions seem to have been first reported in 1965 [7]. Experimental studies showed that combustion of compound droplets with different volatile fluids may be accompanied by violent explosion of the droplets.…”
Section: Introductionmentioning
confidence: 99%